Evaluation of varied dietary crude protein and lysine level at 5.7% of crude protein on productive parameters in broiler chickens - Urdaneta Rincón, María; Leeson, Steven (Revista Científica de la Facultad de Ciencias Veterinarias)
An experiment was carried out to evaluate the performance of 1-18 d broiler chickens to dietary crude protein (CP) levels from 170 to 250 g CP/kg diet and the dietary lysine level formulated at 5.7% of CP level. Thus, the dietary lysine level of diets increased as CP increased. Body weight gain of chicks was affected at ages from 1 to 18 days by the CP and lysine levels. Birds fed the most protein diets at ages from 0 to 7 and 7 to 14 days were heaviest (P smaller 0.05) for dietary CP of 25 vs 19 and 17%. Increased body weight gain (0-18 d) (P smaller 0.05) was found with increasing dietary CP from 210 to 250 g CP/kg diet compared to lower CP levels. Dietary treatments had no effect on daily feed intake (g/b/d) when CP levels were 190 to 250 g CP/kg diet (P bigger 0.05). There was a reduced feed intake with dietary CP at 170 g CP/kg diet (P smaller 0.05). As dietary crude protein increased there was an increase of about 31% in carcass nitrogen deposition (mg/b/d) when chicks were fed diets from 210 to 250 g CP/kg diet compared to the lower CP diets (P smaller 0.05). A decrease in carcass fat deposition (g/b/d) was found as dietary CP increased from 170 to 250 g CP/kg diet. This study indicates that if lysine to CP ratio is kept constant at 5.7%, maximal productive performance of broiler chickens to 18 days can be achieved among 21 and 25% CP. Choosing among diets will depend mainly on cost of the dietary protein.